Pelatihan Menghafal Mufradat Bahasa Arab Melalui Lagu Anak-anak di RA Bi’tsatul Islamiyah: Training to Memorize of Arabic Vocabuary With Children’s Song At Bi’tsatul Islamiyah Kindergarten - Zulpina Zulpina; Erlina; Isra Hayati Darman; Ria Rafita Supriani (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2022)
This community service program aims to improve students' abilities in learning Arabic, especially memorizing Arabic vocabulary at Bi'tsatul Islamiyah Kindergarten North Panyabungan, Mandailing Natal Regency, North Sumatra. This activity involves partners, namely teachers and students of the Arabic Language Education Study Program at STAIN Mandailing Natal. This activity uses the training method. The activity begins with an initial visit to analyze the situation and needs of the students in the classroom. From the results of the visit, it was agreed that this activity was focused on improving students' abilities in learning Arabic. This is done because this kindergarten has only been established for 2 years and only has one teacher. This activity was carried out for two days, starting from students arriving until students leaving. Monitoring and assessment to follow up on the results of PkM activities is carried out on the last day. The results of this service activity show that after going through several activities and training students are able to understand and memorize Arabic vocabulary easily and with fun. While singing, they are able to name Arabic colors, body parts, family members, and so on. Program pengabdian masyarakat ini bertujuan untuk meningkatkan kemampuan siswa dalam belajar bahasa Arab, khususnya menghafal kosakata bahasa Arab di RA Bi’tsatul Islamiyah Panyabungan Utara Kabupaten Mandailing Natal Sumatera Utara. Kegiatan ini melibatkan mitra yaitu para guru dan mahasiswa Program Studi pendidikan Bahasa Arab STAIN Mandailing Natal. Kegiatan ini menggunakan metode pelatihan. Kegiatan dimulai dengan kunjungan awal untuk menganalisis situasi dan kebutuhan para siswa di kelas. Dari hasil kunjungan tersebut disepakati bahwa kegiatan ini difokuskan pada peningkatan kemampuan siswa dalam belajar bahasa arab. Hal ini dilakukan karena TK ini baru berdiri 2 tahun dan hanya memiliki satu orang guru. Kegiatan ini dilaksanakan selama dua hari, mulai dari siswa datang sampai siswa pulang. Pemantauan dan penilaian untuk menindaklanjuti hasil kegiatan PkM adalah dilakukan pada hari terakhir. Hasil dari kegiatan pengabdian ini menunjukkan bahwa setelah melalui beberapa kegiatan dan pelatihan siswa mampu memahami dan menghafal kosa kata bahasa arab dengan mudah dan menyenangkan. Sambil bernyanyi, mereka mampu menyebutkan warna-warna berbahasa Arab, anggota tubuh, anggota keluarga, dan lain sebagainya.